2020
DOI: 10.2147/cmar.s237181
|View full text |Cite
|
Sign up to set email alerts
|

<p>lncRNA DLX6-AS1 Promotes Proliferation of Laryngeal Cancer Cells by Targeting the miR-26a/TRPC3 Pathway</p>

Abstract: Purpose: Laryngeal cancer is the most prevalent tumor type in head and neck cancers. Early diagnosis is considered as an important strategy for improving prognosis. The lncRNA DLX6-AS1 has been shown to modulate tumor phenotypes in several types of cancer, but the role of DLX6-AS1 in laryngeal cancer and its concrete mechanisms are not clear. Methods: Tissue samples from laryngeal cancer patients and corresponding clinical data were used for detailed analysis. The laryngeal cancer cell lines HEp-2 and Tu-177 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…For instance, in laryngeal cancer, DLX6‐AS1 expression trends towards an elevation in clinical cancer tissues and its depletion obstruct the proliferative activity of HEp‐2 and Tu‐177 cells. 27 Also, increased DLX6‐AS1 is presented in colorectal cancer tissues and depleting DLX6‐AS1 restricts metastasis of colorectal cancer cells and arrests cell phase progression. 28 Besides, oesophageal squamous cell carcinoma specimens express elevated DLX6‐AS1 and DLX6‐AS1 down‐regulation is attributed to depressed cell proliferation and metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in laryngeal cancer, DLX6‐AS1 expression trends towards an elevation in clinical cancer tissues and its depletion obstruct the proliferative activity of HEp‐2 and Tu‐177 cells. 27 Also, increased DLX6‐AS1 is presented in colorectal cancer tissues and depleting DLX6‐AS1 restricts metastasis of colorectal cancer cells and arrests cell phase progression. 28 Besides, oesophageal squamous cell carcinoma specimens express elevated DLX6‐AS1 and DLX6‐AS1 down‐regulation is attributed to depressed cell proliferation and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Explored in other cancers, the inhibitory function of DLX6-AS1 has also echoed with the discoveries in this work. For instance, in laryngeal cancer, DLX6-AS1 expression trends towards an elevation in clinical cancer tissues and its depletion obstruct the proliferative activity of HEp-2 and Tu-177 cells 27.…”
mentioning
confidence: 99%
“…For example, lncRNA SNHG1 promotes cell proliferation in laryngeal cancer through regulating Notch1 signaling pathway [28]. lncRNA DLX6-AS1 promotes the proliferation of laryngeal cancer cells via targeting the miR-26a/TRPC3 axis [29]. LncRNA TUG1 promotes cell proliferation and migration of laryngeal cancer cells [30].…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al . (Refs 2, 32, 50, 74) demonstrated that DLX6-AS1 had increased expression in tumour tissues compared with adjacent normal tissues and in higher clinical stages compared with lower stages (Ref. 50).…”
Section: The Effect Of Dlx6-as1 On Respiratory System Cancersmentioning
confidence: 99%
“…In addition, an in vivo study conducted by Liu et al . (Refs 2, 32, 50, 74) reported that DLX6-AS1 triggered the invasion, and migration of HCC via a mechanistic regulation among miR-513c, cullin 4A (Cul4A), and annexin A10 (ANXA10). Thus, the knockout of lncRNA DLX6-AS1 hindered miR-513c-mediated Cul4A suppression and eventually enhanced the ubiquitination-dependent degradation of ANXA10, thereby inhibiting the incidence and progress of HCC (Ref.…”
Section: The Effect Of Dlx6-as1 On Digestive System Cancersmentioning
confidence: 99%